Impact of Cyber Crime In Society, New Challenges. - Chadha, Sanjeev Kumar (International Transactions in Humanities & Social Sciences, 2010)
The article discusses the impact of cyber crime in society. It mentions its reference to criminal offence committed in a network environment particularly on the Internet which has become a way of life and source of living for people due to their reliance and dependence on it. It notes several offences related to the said crime including digital forgery, cyber pornography and hacking. It also points out that the law handling such transgressions has been codified in the Information Technology (IT) Act of 2000.